Membongkar Strategi Komunikasi Efektif: Analisis Kasus Pada Pekerja Sosial di Lingkungan Urban - mucklis mucklis; Emi Triani; Feni Khairifa (Talenta usu, 2024)
This article aims to explore effective communication strategies implemented by social workers in urban environments through a systematic literature review (SLR) approach. The research employs a qualitative method alongside the SLR approach. Primary sources for this study are articles specifically concerning the theme, while secondary sources include supporting articles, books, and reports. The data collection technique used in this research is document analysis and literature review. Data analysis was conducted using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The findings indicate that communication technology plays a vital role in enhancing interactions between social workers and their clients. The success of communication also heavily relies on cultural sensitivity and the social workers' ability to tailor their messages to the diverse needs and contexts of their clients. Challenges such as building trust and adapting to rapid changes, especially under pandemic conditions, are the primary focus of the discussion. The discussion in this article reveals that effective communication in urban social work involves more than the mere transfer of information; it also encompasses relationship building, client empowerment, and strategy adaptation in response to crises. Successful strategies are those that combine the use of technology with a humanity-based approach to support client autonomy and activate their potential for positive social change.